ANALISIS PENGARUH STOCK SPLIT TERHADAP VOLUME PERDAGANGAN DAN HARGA SAHAM PADA PERUSAHAAN TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2011-2017 - Triono, Afit; Herawati, Aty (SWOT : Jurnal Ilmiah Ilmu Manajemen, 2020)
This research aims to understand the differences in trading volume before and after the stock split, and the differences in stock prices before and after the stock split. The sample was 65 companies listed on the Indonesia Stock Exchange which conducted stock split in the period of 2011-2017. This research examined data of trading volume and stock prices of each company in duration of five days before the stock split and five days after the stock split. The technique to analysed the hypothesis is Wilcoxon Signed Rank Test with 95 percent confident level (α = 0.05). This research evidence shows that if the samples are being tested as a whole, the stock split does not have significant effect on trading volume, but the stock split has significant effects on stock price. The results of this study can be used for companies which aims to do stock split, especially to make investment decision regarding stock split and to determine the stock price. This study also useful for investors as consideration to determine the investment decision regarding stock split